THE INFLUENCE OF MEDIA COMPOSITION TO THE GROWTH OF SCENEDESMUS SP. MICROALGAE IN VARIED MEDIA - Mochammad Fierdaus; Onie Kristiawan (Testing Center for Oil and Gas LEMIGAS, 2015)
Media culture is one of the important factors in the growth of microalgae. Culture medium containsÂ macro and micro nutrition required for the growth of microalgae. Composition of nutrition and nutritionÂ concentrations determine the production of microalgae biomass and nutrient content. The aim of this studyÂ is to evaluate the effect of medium composition variation to Scenedesmus sp growth in laboratory-scale inÂ order to get the optimized composition of media for microalgae Scenedesmus sp. This study was conductedÂ in a laboratory scale. The growth medium that were used in this study were: BBL sm, SS, MN, M4N,Â â€œSederhana 2â€, and â€œSederhana 3â€ medium. The microalgae that were used in this study were mixed cultureÂ Chlorophyceae microalgae which is dominated by Scenedesmus sp. The parameters observed were pH,Â optical density (OD), cell density and temperature. The results show that of the 6 variations of the growthÂ medium used in this study M4N medium is the best medium for the growth of microalgae. At the end ofÂ the operation, cell density of Scenedesmus sp. from M4N medium was 306.83 x 106 cell/mL with a darkÂ green color for the culture. The coefficient growth of Scenedesmus sp. which is grown in M4N medium was 0,36. This is likely to be due to the composition of nutrients in the medium M4N which were more complete than other media.